Emerging sustainable technologies for transformation of gelatin and gelatin-based films - Monsur, Hammed Ademola; Hamid, Anis Hamizah; Asiyanbi-H, Tawakalit Tope; Mirghani, Mohamed Elwathig Saeed; Jaswir, Irwandi; Ahmad Fadzillah, Nurrulhidayah (2017)
Maillard reaction of gelatin from different sources exhibited similar reaction phases – the slow and the fast. Enzymatic degradation of gelatin prior to maillard reaction caused difference in the production of browning products among the species. Fish gelatin hydrolyzate displayed multi-fold increase in browning in the first six hours compared to gelatin hydrolyzates from porcine and bovine. Although, the catalytic effect of Cu2+ during Maillard reaction was relatively similar in all the gelatin samples, Cu2+ affect gelatin hydrolyzates differently. The variation in change in browning index of chymotrypsin digested gelatin in presence of Cu2+ could be valuable for development of efficient UV-spectroscopy method for gelatin differentiation. Future works will investigate the effects of other reaction conditions on change in browning index of enzymatic hydrolysates from gelatin.